Analysis Of Active Power Filters Operating With Unbalanced Loads - Rodrigues Limongi, Leonardo; Roiu, Daniel; Bojoi, Radu; Tenconi, Alberto (Eletrônica de Potência, 2010)
The aim of this paper is to perform an analysis of the shunt Active Power Filter (APF) operating with unbalanced loads. The impact of the load imbalance on the APF performance is mathematically demonstrated and validated with experimental results using a 25 kVA shunt APF prototype. The APF operation in such conditions is affected by the appearance of DC-link voltage ripple at twice the grid frequency. As consequence, the source currents become distorted and the APF performance deteriorates. Based on this fact, a new control scheme is proposed to avoid high voltage ripple in the DC link, without increasing the DC-link capacitance.